A Production Process Efficiency Improvement Model at a MSME Peruvian Metalworking Company - Del Rosario-Malasquez, Luis (2023)
This research study seeks to improve the efficiency of the production processes at a MSME metalworking company operating under the Make to Order (MTO) strategy. For these purposes, the authors first assessed the previous problems reported by the company, detecting a low efficiency rate of 69.56% in its production process, which generated an economic impact at 14.6%. Then, the design of a custom model based on several Lean Manufacturing tools, such as Sort and Set in Order Focused on the 5S, Visual Management Board and Work Standardization, production process efficiency improved by 6.4%, reprocessing experienced a 12.63% reduction, and search times decreased by 24 minutes. which translated into a 5.83% savings for the company. In fact, the proposed model generated positive improvements for the research study.